Formulation and stability of horse oil-in-water emulsion by HLB system - Park, Youn Hyung; Kim, Hyun Jung (Food science and biotechnology, 2021)
Optimal condition was determined to prepare horse oil-in-water (O/W) emulsion stabilized by different HLB system. Span 60 and Tween 60 were used to achieve the predetermined HLB values ranging from 10 to 14 and the surfactant concentrations were adjusted to 10–20%. Fifteen formulated O/W emulsions were characterized by mean particle diameter, zeta-potential (ZP), polydispersity index, and encapsulation efficiency (EE, %). Mean particle diameter decreased with increasing HLB value and surfactant concentration. Particles of the emulsion with HLB 12 and surfactant concentration at 15% were distributed in the size of below 500 nm. The particle diameter and EE (%) of the emulsion with HLB 11 or 12 and surfactant concentration at 15 or 20% were not significantly changed during storage at 40 °C for 15 days. These results suggest the characteristics of horse oil O/W emulsion are dependent on HLB values and surfactant concentration so that affect to emulsion properties during storage.